The role of fouling in optimizing direct-flow filtration module design - Wang, M; Mondal, S; Griffiths, I (Elsevier, 2017)
The local transmembrane pressure (TMP) distribution plays a crucial role in the performance of hollow-fibre microfiltration and ultrafiltration membrane devices. A direct-flow filter comprises an array of hollow fibres encased within a single module. The TMP in each hollow fibre is dependent on the spacing between neighbouring fibres, and evolves with time due to pore clogging by contaminants (fouling). We consider an idealized set-up in which the fibres are undeformable and equally spaced within the device, and study the impact of the pore-blocking phenomena on the TMP during the filtration process. The model is used to evaluate the optimum inter-fibre spacing that maximizes the fluid processed either after a prescribed time or before the filter blocks and its dependence on the membrane permeability and the fouling rate. We show that significant improvements can be made on the operating efficiency of a direct-flow device through careful choice in the fibre spacing during fabrication.